Da natureza à bolsa de valores: identificando a sequência de Fibonacci presente no dia a dia - MARTINS, Tatiara de Nazaré Costa (2022)
The present work highlights the Fibonacci sequence and the number of gold present in various everyday contexts and their relevance in these environments. In this sense, the objective of the work is to present the intrinsic presence of Fibonacci numbers in artistic production, in flora, fauna, in the advertising environment and in the financial market of stock exchanges. To achieve this proposal, a bibliographic review of the main authors that approach the Fibonacci sequence was carried out, considering its definition, properties and applicability. Thus, it was found that the Fibonacci sequence present in natural elements or in human creations always presents visual and aesthetic harmony. This mathematics is observed through its numerical proportions and that these proportions can also be used in the estimation of chaotic and dynamic natures such as the stock market.